Participatory Research in Clinical Studies: An Innovative Approach to Co‐creating Nutritional and Physical Activity Recommendations for Older Adults With Sarcopenia (FOOP‐Sarc Project). - Besora‐Moreno, Maria; Sepúlveda, Cristina; Queral, Judit; Jiménez‐ten Hoevel, Claudia; Pedret, Anna; Tarro, Lucia; Valls, Rosa M.; Solà, Rosa; Llauradó, Elisabet (Health Expectations, 2025)
Background: Participating in co‐creation processes can improve the knowledge, satisfaction and healthcare outcomes of volunteers. However, this methodology is still underused in nutritional clinical studies. Objective: This study aimed to use participatory research as an innovative approach to co‐creating nutritional and physical activity (PA) recommendations for the FOOP‐Sarc project and to assess their usability and volunteers' satisfaction and engagement experience (SEE) during the co‐creation process. Design: The co‐creation process was based on four stages: (s1) co‐ideation, (s2) co‐design, (s3) co‐implementation and (s4) co‐evaluation (Ref.: NCT05485402). Setting and Participants: Thirteen volunteers with sarcopenia were included (stages 1–2 [n = 7], stage 3 [n = 3 intervention, n = 3 control] and stage 4 [n = 13]). Measures: The co‐ideation (s1) and co‐design (s2) stages focused on designing recommendations adapted to the volunteers' preferences; the co‐implementation (s3) stage included the implementation and comparison of the co‐created or standard recommendations for 3 weeks to test the recommendations' acceptance; and the co‐evaluation (s4) stage focused on usability, SEE, and adherence. Results: The volunteers co‐created recommendations for improving sarcopenia according to the barriers identified related to diet and PA. The recommendations' usability and the SEE of volunteers were high in all cases. Conclusions: The participatory research approach used in this nutritional intervention study, demonstrates a high usability of the co‐created recommendations for sarcopenia and high SEE of the volunteers, particularly in the volunteers who participated in co‐ideation (s1) and co‐design (s2), the most key stages of the co‐creation process. Patient or Public Contribution: The volunteers in this study participated in the co‐creation of nutritional and PA recommendations to improve sarcopenia, which they must subsequently follow. Trial Registration: ClinicalTrials.gov identifier: NCT05485402.